Socioeconomic lifecourse influences on women's smoking status in early adulthood. Issue 3 (13th February 2006) - Graham, Hilary; Francis, Brian; Inskip, Hazel M; Harman, Juliet; ,
Abstract : Study objective: To incorporate women's domestic trajectories and circumstances into analyses of the socioeconomic influences on women's smoking status (current and former smoking) in early adulthood. Design: Cross sectional survey Setting: Southampton, UK. Participants: 8437 women aged 25–34 recruited from 1998–2002 via patient lists of general practices Main results: Domestic lifecourse factors contributed to the odds of being a current smoker and former smoker in models that included conventional measures of the socioeconomic lifecourse. Early motherhood, non-cohabitation, and lone motherhood increased the odds of smoking; early motherhood and non-cohabitation reduced the odds of former smoking. For example, relative to childless women, odds ratios (OR) for women who had become mothers <20 years were 1.71 for smoking and 0.76 for former smoking. The effects of education and current SEP remained strong with the inclusion of childbearing and cohabitation variables for both outcomes. For instance, compared with women in education to age ⩾22, the odds ratio for smoking for those leaving school ⩽16 was 3.37 and for former smoking was 0.42. Conclusions: Both the conventionally measured socioeconomic lifecourse and the domestic lifecourse contributed separately to the odds of smoking and former smoking, suggesting that lifecourse analyses should incorporate women's domestic circumstances as an important pathway of influence on their smoking status in early adulthood.